2001
DOI: 10.1177/002076400104700406
|View full text |Cite
|
Sign up to set email alerts
|

Help Seeking Behaviour of Psychiatric Patients Before Seeking Care At a Mental Hospital

Abstract: A substantial number of patients suffering from severe mental disorders seek non-professional care. There is a need of studies in community to assess the help seeking behaviour of psychiatric patients and factors associated with it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
140
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 18 publications
13
140
1
1
Order By: Relevance
“…This large group of patients usually visit the traditional faith healers because they are easily approachable and also because they have belief in supernatural cause of mental disorder as well as because of recommendations of relatives and friends. This study is consistence with the earlier research done in India 7,10,11,12 ,which found a signifi cantly higher consultation rate with faith healers in those patients with schizophrenia and delusional disorders. In the current study those patients with psychotic illnesses usually went to faith healers because of the strong belief in faith healers and a belief in black magic as well as in the concept of possession by God.…”
Section: Discussionsupporting
confidence: 90%
“…This large group of patients usually visit the traditional faith healers because they are easily approachable and also because they have belief in supernatural cause of mental disorder as well as because of recommendations of relatives and friends. This study is consistence with the earlier research done in India 7,10,11,12 ,which found a signifi cantly higher consultation rate with faith healers in those patients with schizophrenia and delusional disorders. In the current study those patients with psychotic illnesses usually went to faith healers because of the strong belief in faith healers and a belief in black magic as well as in the concept of possession by God.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the presentation of psychotic disorders more in the relatively younger age group (<40 years) has also been reported by Barua A, Pradhan SC and Chadda RK et al in the past. [14][15][16] This distribution in this study is highly skewed toward males (69%), which might be attributed to the prevailing gender bias in Indian society, where the illness of a male member is taken more seriously than that of a female patient. But in contrast it was found that females were more affected than males which are cited by Barua A, Shankar H et al study.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Since the decision of where to seek help involves both patients and relatives, health education efforts should target all members of the community.…”
Section: Discussionmentioning
confidence: 99%